Role of reinsurance in Natural Catastrophes - Kataev, Egor; Ducháčková, Eva, 1958-; Daňhel, Jaroslav, 1943-2025; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
This work examines what such reinsurance is and why such firms and corporations areneeded, as well as their role in large natural disasters. We will consider what reinsuranceis inherently, what types of reinsurance and contracts exist, we will also consider whatare natural disasters and their various types, and also what natural disasters are affectedby the three main regions, America, Asia and Europe. The main purpose of this work willbe to understand why the scope of reinsurance is more risky than insurance. Consider, asan example, one of the biggest incidents of Hurricane Katrina, which affected the wholeinsurance industry.
Vedoucí práce: Eva Ducháčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses